Business Licensing Reforms : Insights from Selected Country Experiences - Molfetas, Aris (World Bank, Washington, DC, 2019)
This publication provides a collection of case studies documenting successful licensing reforms in five jurisdictions. These case studies complement previous publications of the World Bank Group in the areas of business registration, licensing, and inspections, such as the 2006 publication “Business Licensing Reform: A Toolkit for Development Practitioners” and the 2009 publication “Licensing Case Studies for the Tourism Sector.” The 2006 publication provided both an overview of the phases and approaches as well as specific examples of licensing reform. This collection of case studies discusses additional examples of such reforms by exploring policies, institutions, and procedures as well as innovative approaches to licensing reform to inform development practitioners and governments on practices and solutions in this critical regulatory area.